Sexual Violence and Armed Conflict - Leatherman, Janie (War and conflict in the modern world, 2011)
"Every year, hundreds of thousands of people become victims of sexual violence in conflict zones around the world, most of them women and girls; in the Democratic Republic of Congo alone, approximately 200,000 have faced sexual violence since 1998, and those attacks continue to devastate Eastern Congo in particular, leading to the systematic collapse of safe space. This book offers a comprehensive analysis of the causes and consequences of, as well as responses to, sexual violence in contemporary armed conflict. It explores the functions and effects of wartime sexual violence as part of a global political economy of violence. To understand the motivations of the men (and occasionally women) who perpetrate this violence, the book analyzes the role played by systemic and situational factors such as patriarchy and militarized masculinity in a tangled web of plunder and profit. Difficult questions of accountability are tackled; in particular, the case of child soldiers, who often suffer a double victimization when forced to commit sexual atrocities and other crimes. The book concludes by looking at strategies of prevention and protection as well as an ethics of caring to support the rehabilitation of survivors and their reintegration into family and community life. Sexual violence in war has long been a taboo subject but, as this book shows, new and courageous steps are at last being taken--at both local and international levels--to end what has been called the "greatest silence in history." "--P. [4] of cover